Colorimetric Detection of Escherichia coli Based on the Enzyme‐Induced Metallization of Gold Nanorods. Issue 18 (21st March 2016) - Chen, Juhong; Jackson, Angelyca A.; Rotello, Vincent M.; Nugen, Sam R.
Abstract : A novel enzyme‐induced metallization colorimetric assay is developed to monitor and measure beta‐galactosidase ( β ‐gal) activity, and is further employed for colorimetric bacteriophage (phage)‐enabled detection of Escherichia coli ( E. coli ). This assay relies on enzymatic reaction‐induced silver deposition on the surface of gold nanorods (AuNRs). In the presence of β ‐gal, the substrate p ‐aminophenyl β ‐d ‐galactopyranoside is hydrolyzed to produce p ‐aminophenol (PAP). Reduction of silver ions by PAP generates a silver shell on the surface of AuNRs, resulting in the blue shift of the longitudinal localized surface plasmon resonance peak and multicolor changes of the detection solution from light green to orange‐red. Under optimized conditions, the detection limit for β ‐gal is 128 pM, which is lower than the conventional colorimetric assay. Additionally, the assay has a broader dynamic range for β ‐gal detection. The specificity of this assay for the detection of β ‐gal is demonstrated against several protein competitors. Additionally, this technique is successfully applied to detect E. coli bacteria cells in combination with bacteriophage infection. Due to the simplicity and short incubation time of this enzyme‐induced metallization colorimetric method, the assay is well suited for the detection of bacteria in low‐resource settings. Abstract : A novel multicolorimetric assay is developed to monitor and measure β‐galactosidase activity, which can serve as an indicator for the colorimetric phage‐enabled detection of Escherichia coli . This assay relies on enzymatic‐induced silver deposition on nanorods and is well suited for the bacteria detection in low‐resource settings.